Distance Education becomes Moral Distancing in UNAM’s SUAyED. Towards a Gender approach - Elenes, Evelyn (IJRDO- Journal of Educational Research, 2017)
This dissertation problematizes the conventional arithmetic measurement as a specific resource to explain the studies of abandonment in the Distance Education System of the UNAM, for which it offers a theoretical concept to be able to explain the Psychosocial situation attitude of abandonment, namely moral distancing. The concept is explained dialectically through two monographs, seen from a gender perspective, of students with a failed trajectory in the system. The possibility is left open to solve the problem.